EDUKASI HUKUM PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA SEBAGAI PILAR KETAHANAN KELUARGA SAKINAH DI KELURAHAN SIALANGMUNGGU KOTA PEKANBARU - Angrayni, Lysa; Handayani, Febri; Zuraidah, Zuraidah (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Violence does not discriminate by gender, but it is very clear that violence that occurs in the domestic sphere, namely the household, is very worrying and has become a never-ending conflict. The rate of domestic violence, which tends to increase every year, indicates that victims are beginning to realize that domestic violence is not something that can be normalized, so that victims have the right to fight for the right to a safe and better life. Marriage, which should be a comfortable space for a couple, has instead become the most frightening space for some women. Legal counseling on domestic violence aims to increase public understanding of the forms of violence that occur in the household, their impact on victims, and the legal protection available to those affected. This counseling also aims to prevent domestic violence through education about the rights of victims and legal procedures that can be taken to obtain protection. In addition, this counseling provides information on the role of society in supporting victims of domestic violence and reporting incidents of violence they witness. By understanding the legal and social aspects of domestic violence, it is hoped that the community can be more proactive in addressing and preventing domestic violence. This outreach is expected to increase legal awareness and create a safer and more supportive environment for victims of domestic violence, as well as encourage the creation of a more responsive and effective law enforcement system in handling domestic violence cases. Keywords: Legal Education, Domestic Violence, Peaceful Family